Authors' correction for Western Pacific Surveillance and Response, 2015, 6(3):3–6 - Editorial Team, WPSAR (Western Pacific Surveillance and Response, 2015)
In the article "The use of social media in public health surveillance" by Fung CHF et al, published on 26 June 2015, citations for  for earthquake and tsunami in Japan and earthquake in Haiti in Table 1 under the 'Examples' column were replaced.  This change was made on 28 July 2015, at the request of the authors.